New liposomal doxorubicin nanoformulation for osteosarcoma: Drug release kinetic study based on thermo and pH sensitivity. (12th April 2017) - Haghiralsadat, Fateme; Amoabediny, Ghasem; Sheikhha, Mohammad Hasan; Zandieh‐doulabi, Behrouz; Naderinezhad, Samira; Helder, Marco N.; Forouzanfar, Tymour
Abstract : A novel approach was developed for the preparation of stealth controlled‐release liposomal doxorubicin. Various liposomal formulations were prepared by employing both thin film and pH gradient hydration techniques. The optimum formulation contained phospholipid and cholesterol in 1:0.43 molar ratios in the presence of 3% DSPE‐mPEG (2000). The liposomal formulation was evaluated by determining mean size of vesicle, encapsulation efficiency, polydispersity index, zeta potentials, carrier's functionalization, and surface morphology. The vesicle size, encapsulation efficiency, polydispersity index, and zeta potentials of purposed formula were 93.61 nm, 82.8%, 0.14, and −23, respectively. Vesicles were round‐shaped and smooth‐surfaced entities with sharp boundaries. In addition, two colorimetric methods for cytotoxicity assay were compared and the IC50 (the half maximal inhibitory concentration) of both methods for encapsulated doxorubicin was determined to be 0.1 μg/ml. The results of kinetic drug release were investigated at several different temperatures and pH levels, which showed that purposed formulation was thermo and pH sensitive. Abstract : In this study, we presented the novel simple targeting for PEGylated liposomal formulation with an appropriate mean size of vesicle, encapsulation efficiency, PDI, zeta potentials in order to osteosarcoma treatment. We also employed novel comprehensive formulation to help researchers.